The Association between Audit Quality and Abnormal Audit Fees - Choi, Jong-Hag (Institutional Knowledge at Singapore Management University, 2006)
Using a sample of 9,820 firm-year observations over the 2000-2003 period, this paper examines whether, and how, audit quality proxied by unsigned discretionary accruals is associated with abnormal audit fees, i.e., actual audit fees in excess of expected, normal audit fees. The results of various regressions reveal that the association between the two is insignificant for the full sample, significantly positive for the subsample of clients with positive abnormal fees, and insignificantly negative for the subsample of clients with negative abnormal fees. The above results suggest that auditors’ incentives to compromise audit quality differ systematically for more profitable clients (with positive abonormal fees) vis-a-vis less profitable clients (with negative abormal fees), which in turn leads to the audit fee-audit quality association being conditioned on the sign of abnormal audit fees. Our results are robust to a battery of sensitivity checks. Relevant implications of our results to policy makers and academic researchers are discussed.